2012
DOI: 10.1177/1362361311406296
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with requests by children with autism: the impact of sentence type

Abstract: This study assesses the extent to which children with autism understand requests performed with grammatically non-imperative sentence types. Ten children with autism were videotaped in naturalistic conditions. Four grammatical sentence types were distinguished: imperative, declarative, interrogative and sub-sentential. For each category, the proportion of requests complied with significantly exceeded the proportion of requests not complied with, and no difference across categories was found. These results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 21 publications
1
20
1
Order By: Relevance
“…The present paper constitutes an experimental sequel to Kissine et al [ 33 ]. In line with the results of this study, our first hypothesis is that children with autism will understand indirect requests.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…The present paper constitutes an experimental sequel to Kissine et al [ 33 ]. In line with the results of this study, our first hypothesis is that children with autism will understand indirect requests.…”
Section: Introductionmentioning
confidence: 89%
“…Consequently, some kind of contextual processing is required to comprehend (and then to comply with) the request. What Kissine et al’s [ 33 ] results show, then, is that children with autism do not rely exclusively on the linguistic meaning. Since it is quite unlikely that children in their study engaged in sophisticated reasoning about the speaker’s communicative intentions, their compliance with non-imperative requests probably reveals some kind of egocentric pragmatic processing.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Metonymy comprehension has also been shown to be more preserved than metaphor and to be reliably predicted by receptive vocabulary (Rundblad and Annaz, 2010). 16 Finally, an observational study by Kissine et al (forthcoming) revealed that children with low‐level autism go beyond the utterance's literal meaning in order to interpret it as a request. It is plausible that none of these pragmatic processes requires taking an alternative perspective on the world, although, of course, a more elaborate argument is needed to settle this issue.…”
Section: Pragmatics In Asdsmentioning
confidence: 99%